OPEN INNOVATION MAPPING BASED ON PUBLISHER RESEARCH THROUGH BIBLIOMETRIC ANALYSIS - Yulianti, Prima -; Fahmy, Rahmi; Rivai, Harif Amali; Lukito, Hendra; Syahrul, Laura (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACT Research on open innovation (OI) has increased in recent years, demonstrating its potential in various fields of knowledge. Its linkages with SMEs have attracted the attention of academics. This analysis was conducted from 2018 to 2022. This article aims to evaluate the intellectual structure of open innovation scientific studies, and their relation to various scientific fields, through bibliometric analysis using the Scopus database, publish or perish, the lens, and the VOSviewer software application. The methodology consists of a selective systematic and transparent process divided into four phases: (i) establishing search criteria for research fields, through literature review, (ii) database selection, (iii) application of inclusion and exclusion criteria to the selected documents and explanation of their uses software; and (iv) analysis of results through a scientific output performance approach and bibliometric mapping. The results show an increasing trend of open innovation publications quite a lot, especially in the United Kingdom and the United States, but only a few studies discussing open innovation in SMEs for researchers in Indonesia totaling 121 articles discussing marketing, economics, management and social sciences. So there are many opportunities for researchers in Indonesia. This study contributes to the field by providing an overview of open innovation in the context of MSMEs. Keywords: Open Innovation, Bibliometric, The Lens, VOSviewer